শান্তিবাহিনী, গেরিলা জীবন - মোর্তোজা, গোলাম (ঢাকা : সময় প্রকাশন, 2000)
Social conditions of the people of CHT Region of Bangladesh who had participated in the fights with the government of Bangladesh for the recognition of their rights and later surrendered.
In Bengali.
Keywords: Chittagong Hill Tracts (Bangladesh : Region) -- Social conditions